Analisis Efisiensi Operasional, Manajemen Risiko, dan Pengelolaan Sumber Daya terhadap Keberlanjutan Kinerja Keuangan Perusahaan di Indonesia - Judijanto, Loso (Westscience Press, 2024)
This study investigates the effects of Operational Efficiency, Risk Management, and Resource Management on the sustainability of corporate financial performance in Indonesian companies. A quantitative research approach was employed, using data from 170 companies across various industries. The data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that all three variables have a significant positive impact on financial sustainability. Operational Efficiency emerged as the most influential factor, followed by Risk Management and Resource Management. These results highlight the importance of an integrated approach to corporate strategy, focusing on improving operational processes, mitigating risks, and optimizing resource allocation to achieve long-term financial stability. The study offers practical insights for managers and policymakers on how to enhance corporate financial sustainability in Indonesia.